2003
DOI: 10.1248/bpb.26.1502
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Fraction of Aralia elata Seemann Enhances Antioxidant Activity and Lowers Serum Lipids in Rats When Administered with Benzo(.ALPHA.)pyrene

Abstract: Aralia elata Seemann, one of the most popular edible mountain vegetables in Korea, is classified as a shrub belonging to a species of Araliaceae. The bark and roots have been used in treating hypoglycemia, ulcer, diabetes, gastritis, colitis and schizophrenia.Quercitrin, a bioactive constituent of Aralia elata Seemann, has been suggested to have effects on heart stimulation and contraction, fungal and virus infections, diabetic cataracts, activation of natural killer cells, and pneumonia. As a pharmacologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
1
10
0
3
Order By: Relevance
“…Our findings suggest that these plant extracts contain the potent compounds for suppression of AhR transformation, which is the initial step to express the multiple toxicity of HAHs and PAHs including dioxins (Fernandezโ€Salguero and others 1996; Vorderstrasse and others 2001; Andersson and others 2002; Moennikes and others 2004). Aralia elata has been traditionally used as folk medicine in Japan and Korea (Satio and others 1993; Chung and Jung 2003; Hu and Wang 2009). Therapeutic effects of the bark and root cortex of Aralia elata against treatment of various diseases, such as diabetes and hepatics, have also been revealed (Chung and others 2005; Hu and Wang 2009), and effective constituents in the bark and root of Aralia elata are saponins, alkaloids, glycosides, and so on (Lee and others 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings suggest that these plant extracts contain the potent compounds for suppression of AhR transformation, which is the initial step to express the multiple toxicity of HAHs and PAHs including dioxins (Fernandezโ€Salguero and others 1996; Vorderstrasse and others 2001; Andersson and others 2002; Moennikes and others 2004). Aralia elata has been traditionally used as folk medicine in Japan and Korea (Satio and others 1993; Chung and Jung 2003; Hu and Wang 2009). Therapeutic effects of the bark and root cortex of Aralia elata against treatment of various diseases, such as diabetes and hepatics, have also been revealed (Chung and others 2005; Hu and Wang 2009), and effective constituents in the bark and root of Aralia elata are saponins, alkaloids, glycosides, and so on (Lee and others 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous chemical agents like B(a)P have been shown to affect cellular lipids in variety of tissues (Chung and Jung, 2003). The combined epidemiological evidences suggested a casual relationship between fat intake and the occurrence of Results are expressed as mean ยฑ S.D for six mice in each group.…”
Section: Discussionmentioning
confidence: 99%
“…The effective components of A. elata included saponins, alkaloids, glycosides, palmitic acid, linoleic acid, etc (Lee et al, 2005). Previous study has shown that ethanol extract of A. elata exhibited antioxidant activity by increasing activities of GST and SOD, and lowered decrease serum lipids in rats, which indicated its strong hypocholesterolemic and hypolipidemic actions (Chung et al, 2003). In vivo studies confirmed that the water extract of A. elata can suppress aldose reductase in STZ-induced diabetic rats (Chung et al, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Aralia elata has been used as folk medicine in Oriental courtiers such as Japan and Korea several hundred years ago (Chung et al, 2003;Hu and Wang, 2009;Satio et al, 1993). The bark and root cortex of A. elata were shown to be able to treat diabetes, hepatics, stomach pain, etc (Chung et al, 2005;Hu and Wang, 2009;Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%